IMPLEMENTASI KETERAMPILAN BERBAHASA MEMIRSA DALAM CAPAIAN PEMBELAJARAN KURIKULUM PROTOTIPE MATA PELAJARAN BAHASA INDONESIA KELAS X PADA PROGRAM SEKOLAH PENGGERAK - Yadi Mulyadi; Wikanengsih Wikanengsih (STKIP Siliwangi, 2022)
This research aimed to analyze out the implementation of viewing skills in the teaching materials of Indonesian in senior and vocational high schools for Sekolah Penggerak Program, starting from the type of viewing skills, the strategy of viewing skills, until the learning step of viewing skills learning. The method used in this research was descriptive. The collection data technique used the document analysis of the instructional goals of Prototype Curriculum and teaching materials Indonesian for senior and vocational schools of Sekolah Penggerak Program. The result of the research showed that the implementation of viewing skills was the step of visual literacy viewing and critical viewing. In the step of visual literacy, the instructional process of viewing skills learning was included in the exploration phase by integrating various strategies to re-write the information, either in the form of summary or infographic. Meanwhile, in the critical viewing phase, viewing skills learning was on the more advanced level by evaluating complex multimodal text with various strategies, understanding the relationship between texts, and making deep analyses with logical and critical argumentation.